Fine-tuning carbapenem resistance by reducing porin permeability of bacteria activated in the selection process of conjugation. Issue 1 (December 2018) - Kong, Hoi-Kuan; Pan, Qing; Lo, Wai-U.; Liu, Xuan; Law, Carmen; Chan, Ting-fung; Ho, Pak-Leung; Lau, Terrence
Abstract Antibiotic resistance is an emerging public health issue. Plasmids are one of the popular carriers to disseminate resistance genes among pathogens. However, the response of plasmid-carrying bacteria to antibiotic treatment and how these bacteria evolve to increase their resistance remain elusive. In this study, we conjugated plasmid pNDM-HK toE. coli J53 recipient cells and selected survivors using different concentrations of the broad spectrum antibiotic meropenem. After selection, transconjugants conferred varying minimum inhibitory concentrations with respect to carbapenems. We sequenced and compared the transcriptomes of transconjugants that exhibited distinct carbapenem susceptibilities, and found that the loss of outer membrane proteins led to antibiotic resistance. Moreover, we identified a novel mutation, G63S, in transcription factor OmpR which moderates the expression of outer membrane proteins. The loss of porins was due to incapability of phosphorylation, which is essential for porin transcription and carbapenem resistance. We also characterized other genes that are regulated byompR in this mutant, which contributed to bacterial antibiotic resistance. Overall, our studies suggest antibiotic pressure after conjugation might be an alternative pathway to promote antimicrobial resistance.